Informal sector taxation and enforcement in African countries: How plausible and achievable are the motives behind? A critical literature review - Favourate Y. Sebele Mpofu (Open Economics, 2021)
Taxation is a fundamental tool for revenue generation, economy building and sustainability, reducing market externalities, regulating trade, stimulating representation and achieving tax justice as well as building state accountability and responsiveness. The informal sector in developing countries has been considered a hindrance to effective domestic revenue mobilisation, hence the rejuvenated focus to bring the sector into the tax baskets. Through a critical literature review, this study sought to identify the varying motivations tabled by the various stakeholders (policymakers, scholars and tax administrators) in literature on the need to administer tax on this sector and to strengthen enforcement and to evaluate the plausibility of these motives critically. Literature search was done through Google scholar and this was also aided by snowballing. The motives were aggregated into five major groups: the magnitude of the sector and revenue implications, growth motive, the governance gains, equity considerations and the boosting of tax morale and compliance in the formal sector. This study, therefore, conducted a profound evaluative analysis of literature on these motivations, pinpointing any voids that future research could address and accordingly sought to contribute to the guidance offered to policymakers on how to improve IS taxation. In order to balance the mobilisation of revenue needs and the sector's contribution to other government objectives such as those outlined in the United Nations Sustainable Goals 1, 8 and 10 on poverty, decent work and economic growth, and reduced inequalities, governments and policymakers need to make an informed analysis.
Keywords: 330; equity; governance; growth; Informal sector taxation; revenue; tax morale